Carotid Thrombosis in a Crack Cocaine Smoker Woman - Mattia Cosenza; Luigi Panza; Anna Paola Califano; Carolina Defendini; Maria D’Andria; Roberto Romiti; Antonio Fabio Massimo Vainieri; Sergio Morelli (Case Reports in Vascular Medicine)
Introduction. We report a case of stroke in a crack smoker with occlusion of the middle cerebral artery and a large thrombus in the carotid artery. Case Presentation. A 34-year-old female presented with left upper arm weakness, associated with paresthesia with onset of symptoms more than 24 hours before. Angio-RM sequences showed an area of ischemia, with occlusion of the M2 segment of the middle cerebral artery. Carotid ultrasound showed a soft plaque with distal end floating. Anticoagulant treatment was started, and seriated ultrasound evaluations showed its gradual dissolution. Conclusions. In atherothromboembolic stroke from carotid thrombosis, repeated ultrasound studies may be useful for either diagnosis and monitoring the efficacy of anticoagulant therapy.